Quranic pillow / Muhammad Danish Azimi … [et al.] - Azimi, Muhammad Danish; Rashidi, Muhammad Khairul Amirin; Zullkiflee, Muhammad Hazim; Mohd Abas, Norazira; Ahmad Fauzi, Muhammad Nur Iman; Basyaruddin, Muhammad Aiman Haikal (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The Quranic Pillow for disabled individual’s elder person offers accessibility and comfort, providing an inclusive means for Quranic learning and reflection. With features like large, tactile buttons or voice command options, it ensures ease of use for those with mobility impairments or visual limitations. Its soft and ergonomic design caters to extended periods of use, fostering a serene environment for spiritual growth and connection. On the other hand, the Quranic Pillow combines tradition with innovation, offering a unique blend of comfort and wisdom. With its plush design and embedded speaker, it transforms any space into a sanctuary for Quranic immersion. Whether used for nightly recitations or moments of contemplation, it serves as a timeless companion on the journey of spiritual enlightenment.